1985
DOI: 10.1007/bf00281990
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the incretin concept

Abstract: Experimental and clinical work over the last 6 years has confirmed and broadened, but also challenged, the incretin concept. The nervous component of the entero-insular axis is still poorly defined, especially the peptidergic nerves, of which several contain insulinotropic regulatory peptides. The incretin effect is preserved after complete denervation of the porcine pancreas. Type 2 (non insulin-dependent) diabetic patients have a significantly decreased incretin effect. GIP (gastric inhibitory polypeptide; g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(138 citation statements)
references
References 99 publications
(69 reference statements)
2
134
0
2
Order By: Relevance
“…These results provided further experimental evidence for the postulated role of the enteroinsular axis in glucose homeostasis [15]. They also established the essential role of incretins [16], or substances secreted in the gut in response to nutrients, in the regulation of secretions of the pancreatic islet hormones. Administration of GLP-I(7-37) and GLP-I(7 36)amide together with a meal in patients with Type II diabetes mellitus (NIDDM) eliminated the postpandrial rise in blood glucose [11,12].…”
Section: Introductionsupporting
confidence: 57%
“…These results provided further experimental evidence for the postulated role of the enteroinsular axis in glucose homeostasis [15]. They also established the essential role of incretins [16], or substances secreted in the gut in response to nutrients, in the regulation of secretions of the pancreatic islet hormones. Administration of GLP-I(7-37) and GLP-I(7 36)amide together with a meal in patients with Type II diabetes mellitus (NIDDM) eliminated the postpandrial rise in blood glucose [11,12].…”
Section: Introductionsupporting
confidence: 57%
“…The term "incretin" refers to a gut hormone that is released by oral glucose and that potentiates glucose-stimulated insulin secretion (6). However, the term may be more general and apply to a gut factor stimulating the endocrine pancreas, even Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that signal transduction initiated by GPCRs and RTKs is organized in mutually related signaling cassettes, leading to crosstalk between the RTK and GPCR signaling pathways (Natarajan et al, 2006). In pancreatic β-cells, in addition to GLP-1 and glucose-dependent insulinotropic polypeptide, insulin, insulin-like growth factor (IGF), and other growth factors are known to regulate insulin secretion as well as proliferation and apoptosis of β-cells (Creutzfeldt and Ebert, 1985;Loreti et al, 1974;Shepherd, 2004). Insulin secretion and proliferation by β-cells are inhibited in model systems in which the insulin receptor (IR), IGF receptor (IGFR), or IRS (IR substrate, an IR and IGFR downstream molecule) are knocked out/down (Da Silva Xavier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%